Biological expressions of early life trauma in the immune system of older adults. - Grace A Noppert; Kate A Duchowny; Rebecca Stebbins; Allison E Aiello; Jennifer B Dowd; Philippa Clarke (PLoS ONE, 2023)
Background Poor immune function is associated with increased risk for a number of age-related diseases, however, little is known about the impact of early life trauma on immune function in late-life. Methods Using nationally representative data from the Health and Retirement Study (n = 5,823), we examined the association between experiencing parental/caregiver death or separation before age 16 and four indicators of immune function in late-life: C-reactive Protein (CRP), Interleukin-6 (IL-6), soluble Tumor Necrosis Factor (sTNFR), and Immunoglobulin G (IgG) response to cytomegalovirus (CMV). We also examined racial/ethnic differences. Findings Individuals that identified as racial/ethnic minorities were more likely to experience parental/caregiver loss and parental separation in early life compared to Non-Hispanic Whites, and had poorer immune function in late-life. We found consistent associations between experiencing parental/caregiver loss and separation and poor immune function measured by CMV IgG levels and IL-6 across all racial/ethnic subgroups. For example, among Non-Hispanic Blacks, those that experienced parental/caregiver death before age 16 had a 26% increase in CMV IgG antibodies in late-life (β = 1.26; 95% CI: 1.17, 1.34) compared to a 3% increase in CMV antibodies among Non-Hispanic Whites (β = 1.03; 95% CI: 0.99, 1.07) controlling for age, gender, and parental education. Interpretation Our results suggest a durable association between experiencing early life trauma and immune health in late-life, and that structural forces may shape the ways in which these relationships unfold over the life course.